1999
DOI: 10.1051/apido:19990504
|View full text |Cite
|
Sign up to set email alerts
|

Economic threshold for Varroa jacobsoni Oud. in the southeastern USA

Abstract: -This research was designed to determine economic thresholds for Varroa jacobsoni mites in mature overwintered colonies under conditions that encourage or discourage mite immigration. Congruent data from the present study and our earlier work suggest that a true late-season (August) economic threshold for mites in the southeastern USA lies within a range of mite populations of 3 172-4 261, ether roll mite levels of 15-38, and overnight bottom board insert mite levels of 59-187 in colonies with bee populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 13 publications
7
53
1
1
Order By: Relevance
“…The share of samples with threshold infestation levels in the ANL apiaries was also significantly lower in comparison to the ALL group (Chi 2 , p = 0.026). However, it should be noted that some of the colonies with high infestation rates of more than 7% (see ANL) were able to survive the winter which is consistent with the suggestion of researchers from the USA and Canada (Delaplane and Hood, 1999;Currie and Gatien, 2006). We have demonstrated that the loss rate of the colonies was also dependent on the number of co-occurring pathogens.…”
Section: Epidemiological Situationsupporting
confidence: 90%
“…The share of samples with threshold infestation levels in the ANL apiaries was also significantly lower in comparison to the ALL group (Chi 2 , p = 0.026). However, it should be noted that some of the colonies with high infestation rates of more than 7% (see ANL) were able to survive the winter which is consistent with the suggestion of researchers from the USA and Canada (Delaplane and Hood, 1999;Currie and Gatien, 2006). We have demonstrated that the loss rate of the colonies was also dependent on the number of co-occurring pathogens.…”
Section: Epidemiological Situationsupporting
confidence: 90%
“…On the other hand, non-infested colonies were probably weakened by the negative effect of repeated fluvalinate applications (Barbattini et al, 1989;Slabezki et al, 1991;Liu, 1992), meaning that the magnitude of the differences between non-infested and infested colonies may have been underestimated. Considering the entire experimental period, the daily finite rates of mite population increase were slightly lower (1.0123) than the ones also obtained in Mediterranean conditions by Kraus and Page [(1995); 1.0137 to 1.0214], Verdú [(1993, 1995) immigration rates (Branco et al, 1999;Delaplane and Hood, 1999)] or genetic (bee strain) variations.…”
Section: Discussionmentioning
confidence: 54%
“…I) were not within the action threshold of ca. 13 mites per 100 bees shown for the region by Delaplane and Hood (1999).…”
Section: Discussionmentioning
confidence: 99%